The Logic Position of State Emergency Law in the Implementation of Regional Head Elections during the Covid-19 Pandemic - Ahmad Siboy; Sholahuddin Al-Fatih (Universitas Negeri Semarang, 2022)
The purpose of this study was to describe the position of the state emergency law as the basis for the issuance of the Government Regulation in Lieu of Law and to examine the consistency of the position of the state emergency law in the implementation of regional elections during the pandemic. This study used normative juridical research with conceptual, statutory, philosophical, and case-study approaches. Sources of legal materials in this study consisted of primary, secondary, and tertiary legal materials. The results showed that the Covid-19 pandemic is declared a non-natural disaster to be qualified as coercive urgency, which is a requirement for enacting the state emergency law. However, there is a logical inconsistency about the Covid-19 pandemic concerning regional elections. On the one hand, the Covid-19 is used as an argument to declare the state in an emergency so that it is necessary to issue a state emergency law in the form of the Government Regulation in Lieu of Law. On the other hand, the regional head election is still be held during the pandemic. If the Covid-19 pandemic is considered a state emergency, the regional head election must be postponed until the pandemic is over.